Malnutrition in India: trends and determinants - Radhakrishna, R.; Ravi, C. (2004)
This paper analyses trends in malnutrition over the past two decades and shows that improvements in nutritional status have not kept pace with the reduction in poverty and the current level of malnutrition is unacceptably high. About half of the pre-school children are malnourished and are exposed to the risk of functional impairments. Malnutrition levels are uneven across states. Some middle income states such as Kerala and Tamil Nadu have comparatively better nutritional achievements than higher income states like Maharashtra and Gujarat, North-eastern states are comparatively better performing states and some of them have even out-performed Kerala. - Reproduced.
Keywords: Malnutrition